2014
DOI: 10.1093/carcin/bgu068
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil and omega-3 polyunsaturated fatty acids suppress intestinal polyp growth by modulating the apoptotic process in ApcMin/+ mice

Abstract: The promotion and progression of carcinogenesis are susceptible to nutritional interventions aimed at counteracting cancer development. Lipid metabolism is essential in the onset and progression of tumors and for cancer cell survival. In this study, we tested the effects of diets enriched with natural compounds, such as olive oil and salmon oil, in mice that spontaneously develop intestinal polyps (Apc(Min/+) mice). For this purpose, we evaluated polyp number and volume, intestinal mucosa proliferation/apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 41 publications
5
33
0
Order By: Relevance
“…There were no differences in polyp number and size in control [tricaprylin-vehicle for B(a)P and olive oil alone] mice. Similar to our observation, Barone et al [47] also found that olive oil-enriched diet reduced the spontaneously developed tumors in the colon to a minor extent. Overall, our findings demonstrate that mice that were treated with B(a)P + olive oil resulted in a decrease in the incidence, size and number of adenomas formed in the colon.…”
Section: 0 Discussionsupporting
confidence: 93%
“…There were no differences in polyp number and size in control [tricaprylin-vehicle for B(a)P and olive oil alone] mice. Similar to our observation, Barone et al [47] also found that olive oil-enriched diet reduced the spontaneously developed tumors in the colon to a minor extent. Overall, our findings demonstrate that mice that were treated with B(a)P + olive oil resulted in a decrease in the incidence, size and number of adenomas formed in the colon.…”
Section: 0 Discussionsupporting
confidence: 93%
“…These findings suggest that elevated basal proliferation of normal gut mucosa may be an important early and predisposing factor in cancer development. As reviewed by Tammariello and Milner (43), a large number of dietary agents have been tested for their chemopreventive benefit in Apc mouse models; among the most effective cancer prevention strategies are those agents that target cell proliferation rates within morphologically normal, but at-risk mucosa (44,45). As discussed by Kim (46), folate restriction alone has the ability to reduce basal proliferation rates in animal tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments were carried out as previously described [4]. Briefly, Apc Min/+ transgenic mice (five-weeks-old), were purchased from Charles River (Calco, CO, Italy) and maintained in controlled conditions and with a free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…Centre Inc., Cincinnati, OH, USA), was reverse transcripted in 20 μL of the final volume at 41 °C for 60 min, using 30 pmol antisense primer for CB1 receptor and β-actin gene (Table 2). Real-time PCR was carried out as previously described [4]. All expression data were normalized by dividing the target amount by the amount of β-actin , used as internal control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation